2017
DOI: 10.1007/s00441-017-2597-9
|View full text |Cite
|
Sign up to set email alerts
|

Allergic airway inflammation induces migration of mast cell populations into the mouse airway

Abstract: Mast cells (MCs) and airway nerves play an important role in allergic asthma. However, little is known about the MCs and their interaction with airway nerves during allergic airway inflammation. This study aims to investigate the distribution and proliferation of MC populations in different lung compartments, along with the association of mast cells with nerve endings, using a house dust mite (HDM) model for allergic airway inflammation. BALB/c mice were exposed to HDM extract intranasally (25 μg/50 μl) for 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Studies have also revealed an increase in the MC TC subtype in the airway submucosa and epithelium of severe, but not mild, asthmatic subjects [34]. In addition, it is notable that the majority of the MCs infiltrating the SMC layer in asthma are of the MC TC subtype [15] and an increased ratio of MC TC over MC T is also supported by studies in animal models of asthma [36,37].…”
Section: Protease Phenotype In Asthmamentioning
confidence: 85%
“…Studies have also revealed an increase in the MC TC subtype in the airway submucosa and epithelium of severe, but not mild, asthmatic subjects [34]. In addition, it is notable that the majority of the MCs infiltrating the SMC layer in asthma are of the MC TC subtype [15] and an increased ratio of MC TC over MC T is also supported by studies in animal models of asthma [36,37].…”
Section: Protease Phenotype In Asthmamentioning
confidence: 85%
“…Migration of MCs to the airways has previously been shown in mouse models of allergic airway inflammation [ 44 ] and the increase in pulmonary MCs is preceded by a recruitment of MC progenitors from the blood into the lung [ 45 ]. For this recruitment to occur, MC progenitors need to express integrin α 4 β 1 and α 4 β 7 , which interact with VCAM-1 on the lung endothelium [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study [ 11 ] demonstrated ventilation with 2% H 2 in the air significantly reduced the mRNA levels of the early growth responsive gene-1 (Egr-1) and chemokine (C-C motif) ligand 2 (CCL2), suggesting that H 2 can affect the progress of inflammation by regulating the transcription of proinflammatory regulatory factors and chemokines. In many diseases, such as airway inflammation and cerebral ischemia, type I hypersensitivity caused by mast cell activation will aggravate the tissue congestion and edema [ 12 , 13 ]. H 2 inhibits the body's inflammatory response by inhibiting Th2 reaction to reduce mast cell activation as well [ 14 ].…”
Section: Mechanisms Of the Action Of Hmentioning
confidence: 99%